If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x/(x-3)+5=2x/(3-x)
We simplify the equation to the form, which is simple to understand
x/(x-3)+5=2x/(3-x)
Reorder the terms in parentheses
+(+1-0.333333333333x)+5=2x/(3-x)
Remove unnecessary parentheses
+1-0.333333333333x+5=+2x+/(+3-x+)
Reorder the terms in parentheses
+1-0.333333333333x+5=+( + 0.666666666667x-2)
Remove unnecessary parentheses
+1-0.333333333333x+5=0.666666666667x-2
We move all terms containing x to the left and all other terms to the right.
-0.333333333333x-0.666666666667x=-2-1-5
We simplify left and right side of the equation.
-1x=-8
We divide both sides of the equation by -1 to get x.
x=8
| -2+18-4=60 | | 2x-6=x-4 | | 27-3(16-20)= | | 2x-5+3x=3 | | -10=4n-12 | | 3x(2x+6)(5x-15)=0 | | -18=8x-95x | | 4(8+h)=44 | | 25=x+13-4x | | W^2+13w-40=0 | | 6m+24-2m=-8 | | 8x-7=31 | | 12x-20=16x-3x-35 | | 0.2(5x+10)=6 | | 48+x+22+5x=56 | | x^2+16x=21 | | 12x-15=14x+5x+10 | | 5-x=x+4 | | 22x-12x+5=35 | | 22x-12x+5x=35 | | 2x-2y=3x-3y | | x+3=-10 | | 6x+2=3y+2 | | 2(2x-3)=7(4x) | | 10x-10=25x+12+3x | | xy=-14 | | (x+1)2=-1 | | Ln(9x)=ln(14)+ln(x-7) | | 5x-10=-25 | | 41=8m+13m | | 7x+3=8x-7 | | 8x+6=20x+30+5x |